A rare case of cryptococcal meningitis with infarction of the splenium of the corpus callosum in an immunocompetent patient: A case report - Sahar Hojat Ansari; Somayeh Rahimzadeh (SAGE Open Medical Case Reports)
Meningitis is a severe infection of the central nervous system. Cryptococcus neoformans is an uncommon fungal agent that can cause meningitis and often manifests unusual symptoms. While this infection is more prevalent in immunocompromised patients, it can also affect immunocompetent patients. A 33-year-old housewife living in the village visited our hospital emergency department complaining of a severe headache and mild fever for 7 days. We diagnosed an unusual occurrence of cryptococcal meningitis with infarction of the splenium of the corpus callosum in a patient who appeared to have a healthy immune system. This disease should be considered in immunocompetent individuals with persistent headache or other neurological findings, even in the absence of overt risk factors.